Trend of Representation of Women in Gastroenterology, Hepatology, and Endoscopy Conferences in Asia - Jalpa Devi; Tanyaporn Chantarojanasiri; Dao Viet Hang; Rashid Lui; Raja Affendi Raja Ali; Amna Subhan Butt; Rohan Raja; Trinh To Tram; Ting Ting Chan; Women in GI Focus Group, Emerging Leaders Committee, Asian Pacific Association of Gastroenterology (JGH Open)
ABSTRACT Objectives Despite progress in promoting gender equality, gender bias remains a significant obstacle for women and hinders their academic advancement. We aim to survey and critically analyze women's representation in conferences and changes over time in various regions of Asian countries. Methods An international survey was conducted with representatives from East Asia (Hong Kong, China, and Japan), South Asia (India and Pakistan), and Southeast Asia (Vietnam and Thailand). The survey collected data on faculty members serving as chairpersons, moderators, speakers, and organizing committee members of annual scientific meetings held between 2018 and 2022. Results A total of 33 conferences were held between 2018 and 2022: 24 in gastroenterology, 5 in hepatology, and 4 in endoscopy across East, South, and Southeast Asia, respectively. The total number of invited faculty members was 4106. Out of 4106, the number of women involved as chairperson, moderator, speakers, and organizing committee was 105, 78, 290, and 146, respectively. The representation of women faculty ranged from 3.8% to 25% in East Asia, 9.2% to 13.5% in South Asia, and 11.8% to 34.3% in Southeast Asia. Overall, the increase in women's participation was minor and statistically non‐significant. However, there was an increase of women's participation as chairpersons, moderators, speakers, and organizing committee members from 14.1% in 2018 to 15.2% in 2022. Conclusion Participation of women in Asian annual conferences in the capacity of chairperson, moderator, speaker, and/or organizing committee member was significantly under‐represented. This under‐representation necessitates targeted measures to enhance women's roles in these meetings, thereby supporting their career advancement.